The Role of Boiler Ash and Chicken Manure on Macro Nutrient Availability and Growth of Maize (Zea mays L.) on Peat Soil - Suswati, Denah; Fadilla, Ulfia; Kusuma, Eka Widiyawati Wijaya; Nuriman, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Peat soils are planting media that possess several chemical limitations, including acidic soil pH, low availability of macro- and micronutrients, and low base saturation, which categorize them as nutrient-poor soils. The use of site-specific ameliorants such as boiler ash and chicken manure as alternative materials to lime can improve soil pH and nutrient availability in peat soils. The objective of this study was to determine the effect of boiler ash and chicken manure application on the availability of macronutrients and the growth of maize (Zea mays L.) in peat soil. The research employed a factorial completely randomized design (CRD) consisting of two factors: the first factor was the rate of boiler ash with four treatment levels, and the second factor was the rate of chicken manure with four treatment levels, each replicated three times, resulting in a total of 48 experimental units. The parameters analyzed included soil chemical properties and plant growth indicators (plant height and stem diameter). The results showed that the combination treatment A2B3 (2000 g boiler ash/polybag + 600 g chicken manure/polybag) significantly increased the availability of N, P, K, Ca, Mg, and Na, as well as improved maize growth (plant height and stem diameter) on peat soil compared to the control treatment.